Upaya Meningkatkan Keterampilan Menulis Tegak Bersambung Siswa Melalui Media Lembar Kerja Peserta Didik Berbasis Guided Writing di Kelas III B SDN Inpres Pampangan - Abdan Syakur; Wahidin Syarif; Milia Sugiarti; Asri Pratiwi (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This research aims to improve students' cursive writing skills through guided writing-based student worksheets in class III B at SDN 145 Inpres Pampangan. This research is classroom action research, the subjects of this research were 22 students consisting of 9 men and 13 women. The implementation of this action was carried out for three weeks, where each week one meeting included learning and assessment. The presentation of the first cycle material began on 14 September 2023 and the first cycle test was on 18 September 2023. The presentation of the second cycle material was carried out on 23 October 2023. The results of the study showed that there were 67.1% (15 students) showing good cursive writing skills. pretty good. Then in the second cycle it increased to 96.3%. The contribution of implementing Guided Writing-based LKPD to improving students' writing skills is very significant, meaning it is in the high category. So it can be concluded that the teacher's ability to apply Guided Writing learning media can improve students' writing skills in Indonesian language subjects in class III B UPTD SDN 145 Inpres Pampangan.